PECULIARITIES OF USING BLOCKCHAIN TECHNOLOGY IN THE FIELD OF INTELLECTUAL PROPERTY MANAGEMENT - TERENYAK, Liliya; КІЗІЛОВ, Андрій (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article discusses the current view on the use of blockchain technology in the field of intellectual property management. Today, blockchain is actively used in various business areas, mainly to improve business processes and reduce costs. The main advantages of blockchain are related to the elimination of intermediaries, data reliability, trust and transparency. Storing transaction information without the need for third-party involvement allows transactions to be completed faster and at lower costs. In today’s intellectual property system, licensing, identification of the right holder, investigation of intellectual property rights infringements, and other actions related to the management of intellectual property rights are mostly performed by third parties. Blockchain eliminates the need for such intermediaries, which reduces the cost of managing intellectual property rights. In addition to all of the above, there are a number of potential problems associated with the technical specifics of the blockchain: immutability of the entered data; blockchain is the subject of controversy due to high energy consumption associated with "mining"; most of the existing publicly available consensus mechanisms in blockchain systems rely on the presence of cryptocurrency in the system, which makes it difficult to develop applications not related to the concept of cryptocurrency; the lack of cryptocurrency-independent consensus mechanisms for public blockchains makes it difficult to separate them from "digital coins". There are also problems with using blockchain that are not specific to the intellectual property sector: the speed of processing blockchain transactions is significantly slower than traditional transaction platforms such as VISA or PayPal); lack of proper regulatory support in the blockchain sector; lack of planning for legal requirements on early blockchain platforms.